Hydrous zirconium oxide modified biochar for in situ remediation of arsenic contaminated agricultural soil. Issue 5 (October 2022) - Zhou, Juanjuan; Liu, Yanwei; Li, Bingqian; Huang, Wenyun; Qin, Junhao; Li, Huashou; Chen, Guikui
Abstract: In-situ immobilization is a fast soil remediation method that can recover the value of As-contaminated land quickly. Hydrous zirconium oxide was reported for its efficient arsenic adsorption properties in wastewater treatment, but has not been reported in soil remediation with As contamination. Herein, hydrous zirconium oxide modified biochar (BC-Zr) was synthesized along with hydrous ferric oxide modified biochar (BC-Fe) and hydrous titanium oxide modified biochar (BC-Ti). After comparing their As(III)/As(V) adsorption performance under diverse conditions, BC-Zr showed superior As-immobilization potential in both simulated water and real soil leachate environment. To evaluate its performance in soil remediation, pot experiments were conducted in real As-contaminated agricultural soil using cowpea ( Vigna unguiculata L.) as an indicator plant. Although all these modified BC could improve the growth of cowpea, the shoot biomass treated by BC-Zr increased by 115.8% than CK, while the As concentration in the stem and leaves decreased by 30.8% and 42.6%, respectively. Interestingly, BC-Zr promoted the root nodule system of cowpea in real As-contaminated soil while BC-Fe and BC-Ti failed. The observation of improved root nodule symbiotic system is significant for further development of soil remediation using in-situ remediation technology. This first successful trial of Zr-based soil amendment indicates the superior As-immobilization property of hydrous zirconium oxide in in-situ remediation of As-contaminated soil, implying the great potential applications of BC-Zr in soil remediation. Graphical Abstract: ga1 Highlights: BC-Zr outstands BC-Fe and BC-Ti in As-immobilization in soil environment. The shoot biomass treated by BC-Zr increased by 115.8% compared with control. BC-Zr addition in soil significantly decreased the As content in the shoot of cowpea.